2019
DOI: 10.1001/jamanetworkopen.2019.18281
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Objectively Measured Sleep Duration and Symptoms of Psychiatric Disorders in Middle Childhood

Abstract: IMPORTANCE The long-term association between sleep duration and mental health in children is currently unknown. OBJECTIVE To investigate the prospective associations between sleep duration and symptoms of emotional and behavioral disorders at ages 6, 8, 10, and 12 years. DESIGN, SETTING, AND PARTICIPANTS This population-based cohort study obtained data from the Trondheim Early Secure Study in Trondheim, Norway. A representative, stratified random sample of children born between January 1, 2003, and December 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 70 publications
5
27
1
4
Order By: Relevance
“…First, short sleep duration negatively affects levels of neurotransmitters that regulate mood and thinking [49]. It also impairs executive functions [50], including working memory, cognitive flexibility, and inhibitory control [51,52]. Second, short sleep duration could be associated with heightened stress reactivity, which has been associated with the activation of the hypothalamic-pituitary-adrenal and the sympatho- Table 3 Combinations of physical activity, sedentary time, and sleep duration and their relationships with other mental health indicators (Continued) No of studies…”
Section: Discussionmentioning
confidence: 99%
“…First, short sleep duration negatively affects levels of neurotransmitters that regulate mood and thinking [49]. It also impairs executive functions [50], including working memory, cognitive flexibility, and inhibitory control [51,52]. Second, short sleep duration could be associated with heightened stress reactivity, which has been associated with the activation of the hypothalamic-pituitary-adrenal and the sympatho- Table 3 Combinations of physical activity, sedentary time, and sleep duration and their relationships with other mental health indicators (Continued) No of studies…”
Section: Discussionmentioning
confidence: 99%
“…Sleep deprivation and sleep disruptions may cause severe cognitive and emotional problems [32,33]. Previous studies reported that inadequate sleep duration caused heightened cardiovascular risk, cerebrovascular disease, psychiatric disorders, and obesity [34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Short sleep duration affects brain activity and neurochemicals that regulate mood and cognitive function [16]. It impairs executive functions [17], such as inhibitory control and cognitive flexibility, that could result in increased irritability, impulsivity, anger and aggression [18,19]. Short sleep duration can also make the maintenance of a healthy lifestyle (e.g., physical activity) more difficult because of subsequent daytime sleepiness, fatigue, and tiredness [20,21].…”
Section: Introductionmentioning
confidence: 99%